HIGH-SPEED ANALOG-DIGITAL CONVERTER WITH ADJUSTMENT OF TIME SHIFT OF SAMPLING PULSE - BORTNYK, GENNADIY; KYRYLYUK, SERGIY; BRYL, MYKHAILO (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The paper proposes a method of expanding the dynamic range of high-speed analog-to-digital converters (ADCs) based on the correction of time shifts of sampling pulses. It is shown that high-speed ADCs with multiphase sampling are built on the basis of turning on several ADC modules in parallel on inputs and signal samples shifted relative to each other. Multiplexing the outputs of the ADC samples makes it possible to increase the sampling frequency by several times. But at the same time, dynamic errors of analog-digital conversion occur due to the occurrence of aperture uncertainty of conversion results in individual ADC modules. The aim of the work is to expand the dynamic range of high-speed ADCs with multiphase sampling by adjusting the phase shifts of sampling pulses.The parameters of the analog-to-digital conversion device with multiphase sampling are determined by the set of parameters of the component blocks of the ADC, as well as the relative spread of these parameters. At the same time, the dominant effect is the aperture uncertainty, which causes the occurrence of amplitude errors, which are numerically equal to the increase of the signal during the aperture time. A scheme for calibrating the time shift in the ADC channel is proposed. The value of the time shift of the signal readings in the studied ADC1 channel is estimated relative to the readings formed in the ADC reference channel. The generated error signal from the output of the digital computer with the help of a feedback circuit through the digital-to-analog converter controls the time delay of the sampling pulses formed in the multiphase pulse generator. Such calibration is performed for each ADC channel. In the operating mode of the device, the time delays formed during calibration correct the time shifts of the ADC sampling pulses. To analyze the effectiveness of the proposed correction method, a model of a high-speed analog-to-digital conversion device based on four channels of 8-bit parallel ADCs was developed. An expression for determining the dynamic range of the ADC under study is given. The research results confirmed that thanks to the developed method, it is possible to expand the dynamic range of the 8-bit high-speed ADC by 15 dB in the high frequency band.
Keywords: high-speed analog-to-digital converters; aperture uncertainty; multiphase sampling; dynamic range